Transforming "Shedets" Into "Keydets": an Empirical Study Examining Coeducation Through the Lens of Gender Polarization - Perdue, Abigail L. (Columbia Journal of Gender and Law, 2014)
On June 26, 1996, a seven-one majority of the U.S. Supreme Court held that the all- male admissions policy at the Virginia Military Institute ("VMI") violated the Equal Protection Clause of the Fourteenth Amendment. United States v. Virginia resulted in more than a mere change to an admissions policy; it fundamentally altered VMI’s cultural landscape and had far-reaching implications on the Institution and its student body. As such, United States v. Virginia raised many difficult questions but provided few answers. First and foremost, what would it mean to be a woman at VMI, and how high a price would female cadets have to pay to be labeled "keydets" who deserve to be at VMI instead of "’shedets "? In an attempt to answer these complex questions, I collaborated with a sociologist and psychologist to survey VMIs student body via an anonymous online questionnaire. Three hundred sixty-four students responded, including 311 men and 53 women. This article is the first in a series arising from the empirical data collected in our quantitative impact analysis, which, to my knowledge, is the first and only study of its kind to illuminate the "not-so-happily-ever-after" of VMI’s long and complex litigation story. In this article, I examine the perceived impact of coeducation, perceptions of why members of the opposite sex attend VMI, pressures to conform to prescriptive gender stereotypes of how feminine or how masculine a cadet should be, and perceptions of an expected adverse reaction to perceived violations of gender boundaries. The article illuminates the impact qf gender polarization on the gender identity formation of male and female cadets. It paints a picture of male cadets fiercely defending their traditionally masculine domain and the power and privilege that they derive from it. Fifteen years after the onset of coeducation, many male cadets still perceive female cadets as intruders who are more masculine than non- VMI women. To assimilate into VMI ’ stronghold of masculinity, "otherized" female cadets often employ gender strategies, such as emphatic sameness, to avoid accepting the demeaning status offeminine "shedet" within VMI’ androcentric and gender polarized environment. Yet, in so doing, female cadets may inadvertently forfeit a vital part of theirfeminine gender identities. What remains unclear, however, is whether the price of assimilation comes at too high a cost.